Skin cancer classification for seven types of skin lesions - Rahman, Md. Tawsifur; Azad, Md. Siam Sadman; Muhtasim, Ali (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.